Female and male student teacher’s motives in choosing teaching as a career - Repblicha Astriyadi (Institute of Information Technology and Social Science (IITSS), 2024)
This quantitative study investigates the motives influencing male and female student teachers to pursue teaching careers at a public university in Jambi Province, Indonesia. Utilizing a survey design, the research examined altruistic, intrinsic, and extrinsic motivational factors among 217 first-year students from English (n=114) and Mathematics (n=103) education programs, comprising 172 females (79.3%) and 45 males (20.7%). A twelve-item Likert-scale questionnaire adapted from established international instruments was employed to measure three motivational categories: altruistic (social utility and desire to help society), intrinsic (job activity itself and interest in teaching), and extrinsic (material benefits and external rewards). Data were analyzed using descriptive statistics, including frequency distributions and percentage comparisons. Findings revealed that across all participants, the highest-rated motives were